Synthesized dimers increased herbicidal activity with lowered volatility. (June 2020) - Ding, Guanglong; Tang, Jingyue; Zhang, Wenbing; Li, Yanran; Niu, Junfan; Wang, Weichen; Huo, Hong; Li, Jianqiang; Cao, Yongsong
Abstract: Auxinic herbicides are widely used to control broadleaf weeds in cereal crop fields due to their excellent herbicidal activities. However, volatile drifting caused by their high vapor pressures is a great threat to neighbouring susceptible crops and environment and severely limits auxinic herbicide applications. In this study, a series of auxinic herbicide dimers were synthesized using 2, 4-D, dicamba and MCPA as monomers to reduce their vapor pressures. The results showed that all of the dimers significantly reduced volatilities due to larger molecular weight. The dimers linked with two ester bonds had 2-fold higher herbicidal efficacies than their corresponding monomers in filed experiments. The dimers linked with amide bonds appeared to function as contact action and systemic action herbicides. The dimers, 3a-2(ethane-1, 2-diylbis (2-(2, 4-dichlorophenoxy)acetate)), 3a-4(2-((2-(2, 4-dichlorophenoxy)acetyl)thio)ethyl 2-(2, 4-dichlorophenoxy)acetate), 3b-2(ethane-1, 2-diylbis(2-(4-chloro-2-methylphenoxy)acetate)) and 3c-2(ethane-1, 2-diylbis(3, 6-dichloro-2-methoxybenzoate)) significantly increased the efficacies and reduced volatilities, thus could be developed as potential novel postemergence herbicides. Graphical abstract: Image 1 Highlights: All the synthetic dimers showed much lower volatilities than their monomers. Some dimers showed high activities in both greenhouse and field test. The dimers with -NH- showed different inhibitory phenotype from their monomers. The linkers in prepared dimers had great effects on physicochemical properties. The dimers could reduce the negative effects on environment and non-target crops.